Successful Treatment of Actinomycetoma with Combination of Cotrimoxazole and Tetracycline - Verdy, Verdy; Dewi, Vina Ajeng Puspa; Budiyanto, Arief; Siswati, Agnes Sri (Faculty Of Medicine Airlangga University, 2015)
Background: Actinomycetoma is an infection of chronic granulomatous disease on the skin, subcutaneous tissue, fascia, and bone, occured after trauma because of bacteria innoculation. Clinical features seem painless nodules, abscess, fistula, and sinus with granulated discharge.Gold standard treatment for actinomycetoma is cotrimoxazole. Combination therapy with other antibiotic is needed to prevent resistance and improve therapeutic efficacy. Purpose: To discuss successful treatment of actinomycetoma with combination of cotrimoxazole and tetracycline Case: A 19-years-old woman had complained of chronic post-traumatic wounds since two years ago. Dermatological examination showed multiple painless nodules, sinus, and discharge on right dorsum pedis. Histopathological examination demonstrated sinus in dermis, suppurative granulomas, and SplendoreHoeppli phenomenon in dermis layer. Case Management: Combination therapy consist of cotrimoxazole 2x960 mg, that was given for 6 months and tetracycline 4x500 mg, that was given in the first 1 month. No side effects and drug allergy during and/or post treatment was found. After clinical evaluation for 6 months, successful of treatment was obtained and no recurrence was found. Conclusion: The combination therapy of cotrimoxazole for 6 months and tetracycline for 1 month was proven to be effective and no recurrence was found.Key words: actinomycetoma, cotrimoxazole, tetracycline.